Short Communication Investigation of Pine Needles for Pulp/Paper Industry (Biological Sciences - PJSIR, 2006)
Pine needles (pine leaves) were analyzed for their chemical constituents, and the dimensions of the extracted fibres were determined to assess their utilization for pulp making. Cellulose content of pine needles (41%) was comparable to softwood (42%), whereas the lignin content (35.1%) was high as compared to both softwood (28%) and hardwood (20%). Ash content of pine needles (3.2%) was less than wheat straw (4-9%) and comparable to bagasse (1.5-5 %). The average length of the pine needle fibre (13mm) was greater than fibres of sugarcane (1.7 mm), wheat straw (1.4 mm) and esparto (1.2mm), but less than cotton (30 mm). The average diameter of pine needle fibre (32 ìm) was greater than all the common fibres used for papermaking.